Menggali Penyebab Rendahnya Hasil Belajar Matematika di Kelas V SD Negeri 001 Tanjung - Nahdania, Sri; Ain, Siti Quratul (Jayapangus Press, 2024)
The low mathematics learning outcomes of elementary school students can reflect a number of problems that need to be addressed to improve the quality of mathematics education. Low mathematics learning outcomes are due to factors that influence students during learning. For this reason, it is important to know the factors that cause the low mathematics learning outcomes of elementary school students. The aim of the research is to describe the factors causing the low mathematics learning outcomes for class V at SD Negeri 001 Tanjung, Kampar Regency. The type of research used in this research is qualitative research with descriptive methods. The subjects in this research were students, homeroom teachers, and class V student guardians at SD Negeri 001 Tanjung. Data collection techniques in this open research use observation, interview and documentation methods with research instruments in the form of observation sheets, interview sheets and documentation review sheets. The data analysis technique used by researchers is the Miles and Huberman model data analysis technique which includes data reduction, data presentation and drawing conclusions. Based on the research results, it can be concluded that there are several factors that cause the low mathematics learning outcomes of class V students at SD Negeri 001 Tanjung, namely internal factors including students' physical health, motivation, attention and psychoemotional interest of students and external factors from the teaching methods used, the learning media provided, the physical environment of the school and the family environment.